Studi Deskriptif Gaya Belajar Siswa Sebagai Penentu Model Pembelajaran Terdiferensiasi - Sudarmanto, Agus (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the learning style to determine the learning model of class X students at SMA Negeri 1 Karangkobar. The type of research carried out is descriptive research. The research steps are initiated by giving a questionnaire to the respondents. The number of respondents in class X amounted to 360 students. After the questionnaire was given, 258 students were returned in full and all the statements in the questionnaire were answered. The questionnaire used was tested with validity and reliability tests. Student learning style is calculated by percentage. Based on the percentage of students' answers to the questionnaire, it was concluded that class X students had an auditory learning style or 42.6%. Students have a kinesthetic learning style or 17.1%. Students who have a visual learning style are 40.3%.